A phase Ib/II study of ivosidenib with venetoclax ± azacitidine in IDH1-mutated myeloid malignancies - Lachowiez, CA; Loghavi, S; Zeng, Z; Tanaka, T; Kim, YJ; Uryu, H; Turkalj, S; Jakobsen, NA; Luskin, MR; Duose, DY; Tidwell, RSS; Short, NJ; et al. (American Association for Cancer Research, 2023)
The safety and efficacy of combining the isocitrate dehydrogenase-1 (IDH1) inhibitor ivosidenib (IVO) with the BCL2 inhibitor venetoclax (VEN; IVO + VEN) ± azacitidine (AZA; IVO + VEN + AZA) were evaluated in four cohorts of patients with IDH1-mutated myeloid malignancies (n = 31). Most (91%) adverse events were grade 1 or 2. The maximal tolerated dose was not reached. Composite complete remission with IVO + VEN + AZA versus IVO + VEN was 90% versus 83%. Among measurable residual disease (MRD)–evaluable patients (N = 16), 63% attained MRD-negative remissions; IDH1 mutation clearance occurred in 64% of patients receiving ≥5 treatment cycles (N = 14). Median event-free survival and overall survival were 36 [94% CI, 23–not reached (NR)] and 42 (95% CI, 42-NR) months. Patients with signaling gene mutations appeared to particularly benefit from the triplet regimen. Longitudinal single-cell proteogenomic analyses linked cooccurring mutations, antiapoptotic protein expression, and cell maturation to therapeutic sensitivity of IDH1-mutated clones. No IDH isoform switching or second-site IDH1 mutations were observed, indicating combination therapy may overcome established resistance pathways to single-agent IVO.